PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT TELKOM CABANG MERUYA JAKARTA BARAT - Sulistio, Raditio; Ardiansyah, Fahri; Budi Utomo, Styo (YBAMB, 2024)
This research was conducted at PT Telkom Meruya Branch, West Jakarta, to analyze the influence of motivation and work discipline on employee performance. The aim of the research is to examine the influence of motivation and work discipline on employee performance to improve employee performance at PT Telkom Meruya Branch, West Jakarta. The benefits of this research are expected to improve the quality of motivation and work discipline on employee performance. This research is quantitative research. This research aims to determine the influence of motivation and work discipline on employee performance at PT Telkom Meruya Branch, West Jakarta. This research uses primary data where data collection uses a questionnaire. In this research, researchers used quantitative analysis and multiple linear regression analysis with the help of SPSS 26. The population in this research was 60 employees. Data analysis used SPSS Version 26. The influence of motivation and work discipline on employee performance, the value of Fcount is 295.886 > Ftable 3.16 with a significance level of 0.000 < 0.05, thus Ho is rejected and Ha is accepted, meaning that there is a positive and significant influence of motivation and work discipline on employee performance at PT Telkom Meruya Branch, Jakarta. West.